Tragic Time in Drama, Film, and Videogames The Future in the Instant - Bushnell, Rebecca; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book explores how classical and Shakespearean tragedy has shaped the temporality of crisis on the stage and in time-travel films and videogames. In turn, it uncovers how performance and new media can challenge common assumptions about tragic causality and fate. Traditional tragedies may present us with a present when a calamity is staged, a decisive moment in which everything changes. However, modern performance, adaptation and new media can question the premises of that kind of present crisis and its fatality. By offering replays or alternative endings, experimental theatre, adaptation, time travel films and videogames reinvent the tragic experience of irreversible present time. This book offers the reader a fresh understanding of tragic character and agency through these new media's exposure of the genre's deep structure. Rebecca Bushnell is the School of Arts and Sciences Board of Overseers Professor of English at the University of Pennsylvania, USA. She has written books on many different subjects, including prophecy in Homer and Sophocles, Renaissance tyrant plays, early modern humanist pedagogy, early English gardening books, and the genre of tragedy.
Preface -- Chapter 1. Time, Choice, and Consequences in Greek and Shakespearean Tragedy -- Chapter 2. Tragic Adaptation and Performance: Undoing the Play -- Chapter 3. Time Travel Films: Replaying Time, Choice, and Action -- Chapter 4. Tragic Time and Choice in Videogames -- Bibliography -- Index -- .
Keywords: Literature-Philosophy.; Motion pictures; Film Theory; Media Studies